Indigenization of Weld Consumables for Grade of Steels withYS ≥ 690 MPa for Underwater Pressure Hull Construction - Nimbalkar, V. M.; Mohape, M; Katkar, Vikas; Pandav, S G; Kumar, Sujeet; Jangir, J M; Dakhole, S K; Panigrahi, J; Roy, A; Chaudhari, D S (IJRDO - Journal of Mechanical And Civil Engineering, 2018)
High strength super structural steel, with an excellent combination of strength, toughness and weldability has been developed over the last two decades to replace conventional  medium carbon steels. Modern submarines and warshipsrequires high strength steel plate in increasing portions of the hull structure for weight reduction, increased payload, and survivability.Naval ship structures are subjected to a complex spectrum of loads and environments. So the structural steel and welding materials used in hull fabrication must demonstrate high fracture toughness for these extreme conditions.With increasing in the use of high strength super structural steel for construction of modern submarines and warships, the welding techniques and welding process have become highly specialised. Developing requisite welding consumables and ensuring quality of weld joints is a challenge to both the weld industry and the shipbuilder. The present paper provides the development of indigenous weld consumables for grade of steels with YS ≥ 690 MPa for sub-marine hull construction and warships. Butt weldingexperiments were being carried out usingindigenous weld consumables and control electrodes for reference. In order to characterize the weldments made by indigenous weld consumables, standard tests were conducted to determine the hardness profile, toughness, tensile properties, diffusible hydrogen, moisture content and coating concentricity etc. The results showthat the properties attained by indigenously developed weld consumables are par with control electrodes.